Semi-solid-state aluminium–air batteries with electrolytes composed of aluminium chloride hydroxide with various hydrophobic additives. Issue 47 (27th November 2018) - Mori, Ryohei
Abstract : Semi-solid-state Al–air batteries with solid electrolytes prepared by mixing AlCl3 ·6H2 O and various hydrophobic additives were prepared and tested. Abstract : Semi-solid-state Al–air batteries with solid electrolytes prepared by mixing AlCl3 ·6H2 O and various hydrophobic additives were prepared and tested. All of the prepared Al–air batteries exhibited higher current 48 hours after battery preparation. This might be due to a decrease in battery resistance as AlCl3 ·6H2 O melted and penetrated into the air cathode as a result of its hygroscopic property. Among the batteries tested, when commercial vaseline and butyl methyl imidazolium hexafluorophosphate were mixed with AlCl3 ·6H2 O and used as the solid electrolyte, the prepared Al–air battery exhibited a stable high current and electrochemical property.